Hepatoprotective Effect of aqueous Rosemary extract on amoxicillin induced hepatocytotoxicity in Syrian Hamster - Daoud, Ali; Morra, Mohamed; Mohamed, Doha (Latakia University Journal -Biological Sciences Series, 2018)
The present study aimed to evaluate the hepatoprotective proprieties of aqueous rosemary extract against amoxicillin induced cytotoxicity in liver tissues of Syrian hamster. Thirty-six mal hamsters divided into six groups of six hamsters each were used. Group 1 (control) was received normal food and water for a period of 6 weeks, group 2 received orally a dose of rosemary extract (220 mg/b.w) daily for sex weeks also. Groups 3 and 4 were orally received an amoxicillin dose at 40 and 50 mg/kg body weight respectively three times/week, while Groups 5 and 6 were received Rosemary extract (220 mg/kg b.w) daily for one week then an amoxicillin dose at 40 and 50 mg/kg body weight in combination with aqueous rosemary extract (220 mg/Kg b.w) for five weeks. Biochemical study showed a significant increase in the levels of ALT (p<0.001), AST (p<0.001), bilrubin, uric acid, and urea (p<0.001) in groups 3 and 4, and a significant decrease in the level of these parameters under rosemary extract ((p<0.01). Moreover, Study of liver sections of experimental groups that received antibody alone revealed that amoxicillin induced moderate to severe indices of hepatic cells necrosis such as congestion, nucleus and plasma membrane distraction with infiltration of white blood cells. In addition, a dilation of the central hepatic arteries, and portal veins were also noted. Liver profile was significantly improved in Rosemary extract treated hamsters. Also, amelioration of ALT, AST, bilirubin, albumin, urea, and uric acid has been detected. The present results suggest that aqueous rosemary extract could be a potent natural herbal product provide a promising hepatoprotective effect against hepatocytotoxicity induced by amoxicillin antibiotic. الدور الوقائي للمستخلص المائي لنبات إكليل الجبل على السمية الكبدية المستحثة بالمضاد الحيوي Amoxicillinعند الهامستر السوري هدفت الدراسة الحالية لتقصي تأثير المستخلص المائي لنبات إكليل الجبل في الإجهاد التأكسدي المستحث بالمضاد الحيوي Amoxicillin في الهامستر السوري. شملت الدراسة 36 حيوان وزعت في ست مجموعات متساوية ضمت كل منها ستة حيوانات:المجموعة (1)شاهدة،والمجموعة (2)جُرعت بخلاصة إكليل الجبل (220 ملغ/كغ من وزن الجسم) مرة واحدة/يوم لمدة ستة أسابيع،والمجموعتان (3 و4) جرعتا بالمضاد الحيوي Amoxicillin بتركيز 40 و50 ملغ/كغ من وزن الجسم على التوالي بمعدل ثلاث مرات أسبوعياً. أما المجموعتان (5 و6)فقد تم تجريعهما بخلاصة إكليل الجبل (220ملغ/كغ) لمدة أسبوع ثم جرعتا بإكليل الجبل بنفس الجرعة بالتزامن مع تجريعهما بالمضاد الحيوي Amoxicillin بتركيز 40و50ملغ/كغ على التوالي لمدة خمس أسابيع.أظهرت الدراسة الكيميائية ارتفاعاً في تراكيز كل من أنزيميALT،وAST(p<0.001)، والبولة، وحمض البول،والبيليروبين(p<0.001) في مصل دم حيوانات المجموعتين الثالثة والرابعة التي جرعت بالمضاد الحيوي Amoxicillin، وانخفاض هذه التراكيز بشكل معنوي (p<0.01) بفعل التجريع بالمستخلص المائي لنبات إكليل الجبل. إضافة لذلك، أظهرت دراسة المقاطع النسيجية لأنسجة الكبد في المجموعات التجريبية التي جرعت بالمضاد الحيوي لوحده، ظهور علامات واضحة إلى شديدة لتنخر خلوي مثل انتباج خلايا الكبد وزوال نوى الخلايا وتكسر الأغشية السيتوبلاسمية، وارتشاح التهابي للعدلات واللمفاويات. إضافة لذلك، لوحظ احتقان وعائي في الأوردة المركزية وفي الأوردة البابية للكبد، وقد استعادة أنسجة الكبد وضعها الطبيعي في الحيوانات التي جُرعت بإكليل الجبل بالتزامن مع المضاد الحيوي.كما لوحظ تحسن واضح في تراكيز ALTوAST، البيلروبين، الألبومين، البولة وحمض البول. تفترض نتائج الدراسة الحالية أن الخلاصة المائية لإكليل الجبل يمكن أن تشكل منتج عشبي طبيعي فعال بخصائصه الوقائية للكبد ضد الإجهاد التأكسدي السام المُحدث بالمضاد الحيوي أموكسيسيللينAmoxicillin.